Revised Myeloproliferative Neoplasms Working Group Consensus Recommendations for Diagnosis and Management of Primary Myelofibrosis, Polycythemia Vera, and Essential Thrombocythemia - Agarwal, Mohan B; Malhotra, Hemant; Chakarborti, Prantar; Varma, Neelam; Mathews, Vikram; Bhattacharyya, Jina; Seth, Tulika; Gyathri, K; Menon, Hari; Subramanian, P G; Sharma, Ajay K; Bhattacharyya, Maitreyee; Mehta, Jay; Shah, Sandeep; Gogoi, P K; Nair, Reena; Agarwal, Usha; Varma, Subhash; Prasad, S V V S; Mishra, Deepak K (Indian Journal of Medical and Paediatric Oncology, 2018)
Myeloproliferative neoplasms (MPNs) are clonal disorders, derived from abnormal hematopoietic stem cells and result in an excessive production of blood cells. This MPN group of conditions encompasses different diseases with overlapping clinical and biologic similarities. The majority of the conventional therapies of MPN are palliative in nature. However, with the discovery of Janus Kinase 2 (JAK2) mutation and development of targeted JAK1/2 inhibition therapy, the therapeutic options in treatment landscape have changed dramatically. This article presents the revised Indian MPNs Working Group consensus recommendations. It highlights and brings into attention about the recent findings that have defined the state of the art of the diagnosis and therapy in the MPN area, including identification of the new driver and prognostic mutations, treatment goals in the management of myelofibrosis and polycythemia vera (PV), role of the recently approved, targeted tyrosine kinase inhibitor ruxolitinib in PV, and special issues such MPN consideration in patients with splenic vein thrombosis and the management of the disease in pregnancy.
Keywords: Essential thrombocythemia Janus kinase; myelofibrosis; myeloproliferative neoplasm; polycythemia vera